Effect of Mimosa pudica Extract on NF-κB Expression in Blastocystis sp. Inoculated Rats - Zirma, Dzakiyyah Nafies; Nofita, Eka; Irawati, Nuzulia; Silvia, Roza; Rahayu, Yanti (Jurnal Biologi Tropis, 2026)
Blastocystis sp. is an intestinal protozoan capable of inducing intestinal inflammation through activation of the Nuclear Factor Kappa B (NF-κB) signaling pathway. Current treatment relies on metronidazole, although its efficacy is limited by variable therapeutic responses and adverse effects. Mimosa pudica contains bioactive compounds with potential antiprotozoal and anti-inflammatory activities. This study aimed to evaluate the effect of Mimosa pudica extract on NF-κB expression in Blastocystis sp.-infected Wistar rats. An experimental post-test control group design was conducted using 30 male Wistar rats randomly assigned to six groups: negative control, positive control, metronidazole (9 mg and 13.9 mg), and Mimosa pudica extract (40 mg and 80 mg). Rats were orally inoculated with 10⁵ Blastocystis sp., followed by treatment. Phytochemical screening and FTIR was performed, and NF-κB expression was analyzed using RT-PCR. Phytochemical analysis confirmed the presence of flavonoids, alkaloids, tannins, and saponins. Administration of Mimosa pudica extract reduced NF-κB expression compared with the positive control. A significant difference in NF-κB expression was observed among the study groups (p = 0.028). These findings suggest that Mimosa pudica extract exhibits antiprotozoal and anti-inflammatory activity and may serve as a potential complementary therapy for blastocystosis through modulation of the NF-κB signaling pathway.